2016
DOI: 10.1159/000448293
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Tuberous Sclerosis Renal Guidelines from the 2012 Consensus Conference: Current Data and Future Study

Abstract: Renal-related disease is the most common cause of tuberous sclerosis complex (TSC)-related death in adults, and renal angiomyolipomas can lead to complications that include chronic kidney disease (CKD) and hemorrhage. International TSC guidelines recommend mammalian target of rapamycin (mTOR) inhibitors as first-line therapy for management of asymptomatic, growing angiomyolipomas >3 cm in diameter. This review discusses data regarding patient outcomes that were used to develop current guidelines for embolizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 28 publications
1
55
0
8
Order By: Relevance
“…The causes of the premature loss of GFR are thought to include acute kidney injury from renal hemorrhage, loss of normal renal parenchyma following embolization or surgery, hypertension, replacement of normal renal cells with angiomyolipomata or cysts during growth and repair, and possibly haploinsufficiency, causing mTOR overactivation, resulting in early loss of nephrocytes (Kingswood, Bissler, et al, ). Also, it has been suggested that damage is caused to normal renal tissue by multiple angiomyolipomata; although GFR can be normal even when there is no recognizable renal parenchyma on imaging.…”
Section: Clinical Aspects and Treatment Of Tsc Renal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The causes of the premature loss of GFR are thought to include acute kidney injury from renal hemorrhage, loss of normal renal parenchyma following embolization or surgery, hypertension, replacement of normal renal cells with angiomyolipomata or cysts during growth and repair, and possibly haploinsufficiency, causing mTOR overactivation, resulting in early loss of nephrocytes (Kingswood, Bissler, et al, ). Also, it has been suggested that damage is caused to normal renal tissue by multiple angiomyolipomata; although GFR can be normal even when there is no recognizable renal parenchyma on imaging.…”
Section: Clinical Aspects and Treatment Of Tsc Renal Diseasementioning
confidence: 99%
“…There is an association between the size of an angiomyolipoma and bleeding, with those 30 mm in diameter and still enlarging at greatest risk of bleeding (Kingswood, Bissler, et al, ). Hence, the recommendation in the International Guidelines for surveillance and management of TSC that angiomyolipomata that are 30 mm in diameter and enlarging should be treated preemptively to prevent hemorrhage (Krueger et al, ), with an mTOR inhibitor as first choice therapy.…”
Section: Clinical Aspects and Treatment Of Tsc Renal Diseasementioning
confidence: 99%
“…Although angiomyolipomas are benign tumors, they are highly vascular and can encounter spontaneous bleeding, usually presenting with abrupt abdominal pain and hematuria. Sudden bleeding of an angiomyolipoma requires embolization, can be life threatening and sometimes lead to renal insufficiency requiring dialysis and/or renal transplant (Kingswood et al, ). Fortunately, the use of mTOR inhibitors is changing the natural history of angiomyolipomas, reducing the size of the lesions in the majority of patients, and preventing major complications in an increasing number of individuals (Bissler et al, ).…”
Section: Clinical Manifestations Of Tsc In Adulthoodmentioning
confidence: 99%
“…There was no systemic treatment available until 2008, at which point mTOR inhibition was introduced as a viable treatment option. [12] Although the treatment has rarely been used in children,[3] either sirolimus (SIR) or everolimus (EVR) is recommended if the AMLs are larger than 3.0 cm. [24] There have been no documented cases detailing the use of SIR or EVR to treat numerous AMLs causing substantial renomegaly and chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Although the treatment has rarely been used in children,[3] either sirolimus (SIR) or everolimus (EVR) is recommended if the AMLs are larger than 3.0 cm. [24] There have been no documented cases detailing the use of SIR or EVR to treat numerous AMLs causing substantial renomegaly and chronic pain. Here, we describe a case of a patient with renal AMLs whose kidneys returned to a normal size following treatment with SIR for 3.5 years.…”
Section: Introductionmentioning
confidence: 99%